(3CYdGe GdSGOI GdCeGLO aj aVd HfGA GdeSGLOs - (3GdeUQj , eMeO Hf Ndjd Hf ZQS GdOjf Hf CMeO,J (B885 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQY HfG GdeSGLO hHYO GdaVd GdChd ai aVd HfG GdeSGLO hGdJQZjH ajgG s
(3BNQgG (B:s
(3hSha EdjgeG GYfGb GdSYGOI ai GdOGQjf gPG BNQ eG bUOJ LeYg ai gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdSjGSI hGdGLJeGYs